1996
DOI: 10.5980/jpnjurol1989.87.923
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Oxybutynin Hydrochloride in the Treatment of Urge Incontinence in the Elderly

Abstract: It is suggested that intravesical oxybutynin hydrochloride is an effective option of therapy for intractable urge incontinence in elderly people, however, the immediate posttreatment cystometrogram was not predictive of the response to intravesical therapy on overactive bladder in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Brendler et al [1989] first reported the treatment of intravesical oxybutynin chloride for neurogenic bladder. Mizunaga et al [1996] reported intravesical oxybutynin with HPC for six healthy volunteers and seven overactive bladder patients. The mechanisms of action of intravesical oxybutynin, still unknown, may be the direct effect on the bladder muscle, topical anesthetic effect, and the indirect effect of absorbed oxybutynin and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brendler et al [1989] first reported the treatment of intravesical oxybutynin chloride for neurogenic bladder. Mizunaga et al [1996] reported intravesical oxybutynin with HPC for six healthy volunteers and seven overactive bladder patients. The mechanisms of action of intravesical oxybutynin, still unknown, may be the direct effect on the bladder muscle, topical anesthetic effect, and the indirect effect of absorbed oxybutynin and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a subset patients who do not respond to oral medication or who experience intolerable systemic side effects from these drugs [Massada et al, 1992;Mizunaga et al, 1996;Buyse et al, 1998]. There is, however, a subset patients who do not respond to oral medication or who experience intolerable systemic side effects from these drugs [Massada et al, 1992;Mizunaga et al, 1996;Buyse et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that plasma concentrations of oxybutynin after intravesical HPC-modified oxybutynin were significantly lower than that after instillation of oxybutynin alone, and the effect of HPC-modified oxybutynin lasted longer than oxybutynin alone. Moreover, favorable clinical effects were achieved, and no AEs were observed for more than six months during medication periods [40]. In our first report on modified intravesical oxybutynin chloride in adult patients [41], six patients were treated with modified intravesical oxybutynin chloride.…”
Section: Modified Intravesical Oxybutynin Chloridementioning
confidence: 93%